Alteración del patrón de enfermería reposo sueño y su influencia en el rendimiento académico en estudiantes del segundo curso de la Unidad Educativa Ventanas. octubre 2018 – abril 2019 - Roca Chucad, Yuleisy Lourdes (2019)
The present research work deals with the nursing sleep rest pattern and its influence on the academic performance of students in the second year of the Ventanas Educational Unit, which will allow us to know about this problem, the relationship between both variables and its importance during the academic stage since the lack of rest and the lack of hours of sleep have been evidenced for some time. The modality of this research is quali - quantitative, correlational explanatory type, cross - sectional, aims to determine the influence of the nursing sleep rest pattern on the academic performance of students in the second year of the windows educational unit, during the period October 2018 - April 2019. Applying a rigorous methodology that allows the collection of information in order to obtain real and reliable data. Through this investigative work it is concluded that the nursing sleep rest pattern if it influences the academic performance, since the adolescents stated that during the academic hours they feel fatigue, exhaustion, weakness and this confirms that there is an alteration of the nursing pattern rest sleep Through the applied instruments I could notice that the study population is affected by the alteration of sleep rest pattern, as well as the lack of knowledge of the adequate hours destined for a good rest sleep